Clinical Presentation and Periodontal Management of a Case Mimicking Generalized Aggressive Periodontitis in a Patient With Sarcoidosis: A Case Report. Issue 1 (1st February 2016) - Smitha, K.; Pradeep, A.R.; Natrajan, M.; Shilpa, K.; Janitha, S.; Smitha, G.P.
Abstract : Introduction: Sarcoidosis is a multisystem disease of unknown etiology characterized by the presence of non‐caseating granulomas with rare manifestations in the oral cavity and with only ≈75 cases having been reported in the literature, including the present case. Case Presentation: A 23‐year‐old Indian female presented with the chief complaint of red, enlarged, bleeding gums and loosened teeth with increasing gaps between the teeth over the past 2 years. Clinical examination revealed moderate to severe generalized breakdown of the periodontium. The medical history revealed that the patient was diagnosed with sarcoidosis involving the joints of the extremities, had undergone long‐term clinical treatment for 18 years, and was considered to be under clinical control only 1 month before reporting for dental treatment. Histopathology of biopsy specimen obtained from palatal gingiva indicated the presence of focal areas of non‐caseating granulomas, which was compatible with sarcoidosis. The patient was diagnosed with periodontitis as a manifestation of systemic disease attributable to sarcoidosis. She was managed surgically for periodontitis and was followed up for 12 months. She showed no progression of periodontal disease. Conclusion: Careful review of medical history and close monitoring of intraoral conditions are critical for patients with a history of sarcoidosis.